DAMPAK GRATIS ONGKOS KIRIM DALAM GAYA BELANJA GEN Z DI BATANG-PEKALONGAN - Muhammad Bayu Anggoro Rizkiyanto; Kharits Syauqiy; Versiandika Yudha Pratama (EBID: Ekonomi Bisnis Digital, 2025)
This study aims to analyze the impact of free-shipping promotions on the shopping behavior of Generation Z in the Batang and Pekalongan regions. This generation is known for being highly price-sensitive and active users of e-commerce platforms such as Shopee and TikTok Shop. The research employs a descriptive qualitative approach, with data collected through in-depth interviews involving informants aged 17–27 who are actively engaged in online shopping. Data were analyzed thematically by categorizing participants’ responses based on attitudes, subjective norms, and perceived behavioral control, following the framework of the Theory of Planned Behavior (TPB). The results indicate that free-shipping promotions significantly influence Generation Z’s purchase intentions and decisions. These promotions are perceived to provide economic benefits, increase shopping interest, and shift consumer behavior from physical stores to digital platforms. Furthermore, consistent free-shipping offers help build loyalty toward specific e-commerce platforms. The findings highlight that free-shipping strategies serve as an effective marketing tool to attract young consumers while also contributing to changes in local economic patterns in the digital era.